Effect of Ag2O substituted in bioactive glasses: a synergistic relationship between antibacterial zone and radiation attenuation properties - Tekin, H. O.; Al-Buriahi, Mohammed; M. Issa, Shams A.; Zakaly, Hesham M. H.; Issa, Bashar; Kebaili, Imen; Badawi, Ali; Karimi, M. K. A.; Matori, Khamirul Amin; Mohd Zaid, Mohd Hafiz (Elsevier, 2021)
In this study, a promising relationship between antibacterial zone and radiation attenuation properties was investigated in Ag2O doped bioactive glasses with a chemical composition of xAg2O–20Li2O–25TeO2-(55-x)B2O3 (where x = 0, 0.5, 1.0, 1.5, and 2.0 mol%). For this aim, a wide-ranging radiation attenuation characterization procedure was performed on Ag2O substituted bioactive glasses. The general-purpose Monte Carlo code MCNPX (v.2.7.0) was used to model bioactive glasses. The mass attenuation coefficients were calculated using a gamma-ray transmission setup. The coefficients obtained were used to determine other important attenuation properties. Finally, for particular behaviors, exposure (EBF) and energy absorption (EABF) build-up factors were calculated for specific attitudes of Ag2O substitutions in bioactive glasses during the interaction process. The results showed that there is direct relationship between Ag2O substitution amount and radiation attenuation properties. In addition to its well-behaviors on inhibition zone against bacterial occurrences, it can be concluded that increasing Ag2O would increase the gamma-ray attenuation properties of studied bioactive glass system.